2003
DOI: 10.1094/phyto.2003.93.3.278
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Location ofPrune dwarf virusin Almond Sections by In Situ Reverse Transcription-Polymerase Chain Reaction

Abstract: In situ reverse transcription-polymerase chain reaction (RT-PCR) was used in young leaves (from trees and in vitro shoots) and flower buds of almond (Prunus dulcis), a stone fruit, for cellular location of Prune dwarf virus (PDV, a member of the genus Ilarvirus). Sections obtained from samples fixed in formaldehyde and embedded in paraffin were refixed in formaldehyde to increase tissue preservation in the RT-PCR steps. The coat protein gene of PDV was used as the target to produce a cDNA copy that was amplifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 28 publications
2
8
0
Order By: Relevance
“…Samples from plantlets rooted using 0.005 or 0.4 mM IBA were collected from isolated roots along 10 d after hormonal induction. Tissues were fixed and sectioned following the procedure described by Silva et al (2003) for almond shoots. A general staining was performed by toluidine blue (Feder and O'Brien, 1968) for 5 min at 55 °C followed by washing with water and drying.…”
Section: Histology Of Adventitious Rootsmentioning
confidence: 99%
See 1 more Smart Citation
“…Samples from plantlets rooted using 0.005 or 0.4 mM IBA were collected from isolated roots along 10 d after hormonal induction. Tissues were fixed and sectioned following the procedure described by Silva et al (2003) for almond shoots. A general staining was performed by toluidine blue (Feder and O'Brien, 1968) for 5 min at 55 °C followed by washing with water and drying.…”
Section: Histology Of Adventitious Rootsmentioning
confidence: 99%
“…The choice of the auxin type and concentration can differ according to the specific culture conditions involved. The rooting of some woody species including Prunus can be also improved under darkness during the first week (Sriskandarajah et al 1982, Rugini et al 1993, Caboni et al 1997.…”
Section: Introductionmentioning
confidence: 99%
“…Megagametophytes containing embryos and isolated zygotic embryos in diVerent developmental stages were Wxed and paraYn-embedded as described in Silva et al (2003), with the following modiWcation: tissues were Wxed in freshly prepared 4% paraformaldehyde and 0.25% glutaraldehyde pH 7.4 sodium phosphate buVer (PBS). In situ reverse-transcription PCR was generally performed as described in Silva et al (2003), with some modiWcations.…”
Section: Reverse Transcription Pcr (Rt-pcr)mentioning
confidence: 99%
“…In situ reverse-transcription PCR was generally performed as described in Silva et al (2003), with some modiWcations. After sectioning, samples were immersed in Histo-Clear for 10 min and then rehydrated through a graded ethanol series.…”
Section: Reverse Transcription Pcr (Rt-pcr)mentioning
confidence: 99%
“…The symptoms of PDV infection vary through the year, and the severity of the infection is directly related to the orchard management. Ilarviruses are known to spread through pollen or seeds and recently it was shown that PDV is carried inside almond pollen grains (Silva et al 2003). Because most almond varieties are self-incompatible (Boskovic et al 1997), cross-pollination is required for fruit production, which complicates the control of the disease.…”
Section: Introductionmentioning
confidence: 99%